"A luta continua!" On Freedom, Freedoms and the Role of the Church in South Africa with Special Reference to the Uniting Reformed Church in Southern Africa - Hansen, Len; Mahokoto, Sipho (2025)
In the context of a colloquium on views of and challenges to freedom across three continents, this essay, from a South African perspective, examines freedom through the lens of philosopher and economist Amartya Sen. It pays particular attention to Sen’s view of the multidimensional and instrumental character of freedom(s). An overview is given of the role of South African Christian churches in the struggle for political liberation prior to 1994, before focusing specifically on the contribution of URCSA. The discussion also includes examples of remaining "unfreedom" in post-1994 South Africa, again as understood through Sen’s framework of instrumental freedoms, URCSA’s ongoing commitment in this regard is then considered. The essay demonstrates that notwithstanding periodic critique to the contrary, URCSA has maintained its prophetic witness through its ministries, and that in these endeavours the multidimensional nature of freedom is consistently acknowledged - often against the backdrop of the Belhar Confession, itself a product of the struggle for political freedom.
Keywords: Amartya Sen; Apartheid; Freedom; South African Church History; Suid-Afrikaanse Kerkgeskiedenis; URCSA; VGKSA; Vryheid